Premature Birth Infants Present Elevated Inflammatory Markers in the Meconium - María Victoria Rodríguez-Benítez; Reyes Gámez-Belmonte; Mercedes Gil-Campos; Cristina Hernández-Chirlaque; Paula R. Bouzas; Fermín Sánchez de Medina; Olga Martínez-Augustin (Frontiers Media S.A., 2021)
Introduction: Prematurity, a well-established risk factor for various intestinal diseases in newborns, results in increased morbidity and mortality. However, the intestinal inflammatory status of preterm (PT) infants has been poorly characterized. Here we have broadly described the intestinal and systemic inflammatory status of PT children.Materials and Methods: Meconium and plasma from 39 PT and 32 full term (T) newborns were studied. Fecal calprotectin, polymorphonuclear leukocyte elastase (PMN-E), TNF, IL-17A, IL-8, IP-10, MCP-1, MIP-1, IL-1β, IL-1α, and E-selectin and the enzymatic activities of myeloperoxidase (MPO) and alkaline phosphatase (AP) in meconium were measured. Plasma levels of AP, hepatocyte growth factor, nerve growth factor (NGF), proinflammatory cytokines, leptin, adiponectin, PAI-1, and resistin were also determined. Correlations with gestational age (GA) and birth weight (BW) were studied.Results: Neutrophil derived PMN-E, MPO and calprotectin were increased in the meconium of PT compared to T newborns, while AP was decreased. No significant differences were found in other inflammatory parameters. Considering data from all children, GA and BW showed inverse correlation with neutrophil markers, while AP directly correlated with BW. Plasma levels of IL-1β and NGF were enhanced in PT infants, and were also negatively correlated with BW. PT children additionally showed neutropenia and decreased adiponectin, leptin, haematocrit, and haemoglobin. These parameters (neutrophils, adiponectin, and so forth) were positively correlated with GA and BW, while IL-8, MCP-1, PAI-1, and plasma AP were negatively correlated. PT children showing postnatal morbidity exhibited increased meconium MPO and MIP-1α.Conclusion: PT neonates present a significant elevation of intestinal inflammatory parameters, characterized by the presence of neutrophil markers, associated with mild systemic inflammation.